2017
DOI: 10.1002/bies.201700170
|View full text |Cite
|
Sign up to set email alerts
|

RNA Decay Factor UPF1 Promotes Protein Decay: A Hidden Talent

Abstract: The RNA-binding protein, UPF1, is best known for its central role in the nonsense-mediated RNA decay (NMD) pathway. Feng et al. now report a new function for UPF1-it is an E3 ubiquitin ligase that specifically promotes the decay of a key pro-muscle transcription factor: MYOD. UPF1 achieves this through its RING-like domain, which confers ubiquitin E3 ligase activity. Feng et al. provide evidence that the ability of UPF1 to destabilize MYOD represses myogenesis. In the future, it will be important to define oth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 42 publications
0
9
0
Order By: Relevance
“…In this context, reduced NMD efficiency permits increased expression of myogenin-a muscle-specific transcription factor involved in muscle differentiation-and consequently, myogenesis (Gong et al, 2009). Furthermore, consistent with the idea that reduced NMD, or NMD factors, in this case, is critical for myogenesis, it was recently demonstrated that the E3 ligase function of the UPF1 protein (Kuroha, Ando, Nakagawa, & Inada, 2013;Kuroha, Tatematsu, & Inada, 2009) targets MYOD, a protein that promotes myogenesis, for ubiquitination and degradation (Feng, Jagannathan, & Bradley, 2017;Takahashi et al, 2008;M. Plank & Wilkinson, 2018).…”
Section: Physiological Variation Of Nmd During Differentiation and Developmentmentioning
confidence: 63%
“…In this context, reduced NMD efficiency permits increased expression of myogenin-a muscle-specific transcription factor involved in muscle differentiation-and consequently, myogenesis (Gong et al, 2009). Furthermore, consistent with the idea that reduced NMD, or NMD factors, in this case, is critical for myogenesis, it was recently demonstrated that the E3 ligase function of the UPF1 protein (Kuroha, Ando, Nakagawa, & Inada, 2013;Kuroha, Tatematsu, & Inada, 2009) targets MYOD, a protein that promotes myogenesis, for ubiquitination and degradation (Feng, Jagannathan, & Bradley, 2017;Takahashi et al, 2008;M. Plank & Wilkinson, 2018).…”
Section: Physiological Variation Of Nmd During Differentiation and Developmentmentioning
confidence: 63%
“…The RNA helicase UPF1 is one of the central molecules in nonsense-mediated mRNA decay (NMD) and Staufen-mediated mRNA decay ( Plank and Wilkinson, 2018 ). UPF1 knockdown could increase the expression of SMAD7 as well as inhibit the activation of the SMAD1/5/8 pathway ( Figure 5D–E ).…”
Section: Resultsmentioning
confidence: 99%
“…UPF1 has been reported to accelerate the decay of RNA. 38 However, a recent report has also suggested the RNA stabilization role of UPF1 in glioblastoma cells. 26 In this study, we identified UPF1 as the molecular chaperone of TTN-AS1, and that it also interacted with NETO2 mRNA in NPC cells.…”
Section: Discussionmentioning
confidence: 99%